Liquid crystal polyarylate polymer, liquid crystal polyarylate fiber and preparation method thereof

By introducing structural units containing polar groups into the liquid crystal polyaryl polymer, dipole interaction and hydrogen bond interaction are used to solve the problem of insufficient surface bonding of liquid crystal polyaryl fibers, achieving high strength, high mold and excellent bonding of fibers, and suitable for high performance composite materials.

CN119081088BActive Publication Date: 2025-03-11YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411554602.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-11
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

In the application of existing liquid crystal polyaryl fibers, due to the insufficient adhesion of the fiber surface, the binding ability with the substrate is limited, which affects its application in the fields of national defense and military industry, aerospace, 5G communications, etc.

Method used

By introducing structural units containing polar groups into the liquid crystal polyaryl polymer, the adhesion of the fiber is enhanced by dipole interaction and hydrogen bond interaction.

Benefits of technology

显著提高了液晶聚芳酯纤维的拉伸强度和模量,并增强了其与其他材料的粘结性,适用于高性能复合材料的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_17
    Figure SMS_17
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of fiber preparation, and in particular to a liquid crystal polyarylate polymer, a liquid crystal polyarylate fiber and a preparation method. The preparation method of the crystal polyarylate polymer is as follows: under an inert gas atmosphere, p-hydroxybenzoic acid, a fluorinated benzoic acid monomer, 2-hydroxy-6-naphthoic acid, and a catalyst are added to acetic anhydride, and heated for prepolymerization; after the prepolymerization reaction is completed, the inert gas atmosphere is maintained, the temperature is raised for polycondensation reaction, acetic anhydride is continuously discharged during the polycondensation reaction, the viscosity of the reaction polymer is controlled, and the liquid crystal polyarylate polymer is obtained after the reaction is completed. The liquid crystal polyarylate polymer is melt-spun to obtain a liquid crystal polyarylate fiber. The liquid crystal polyarylate fiber has good mechanical properties and low water absorption, and its excellent interface composite performance makes it have high adhesion to other materials, and has broad application prospects in the fields of 5G communications and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a liquid crystal polyarylate polymer, a liquid crystal polyarylate fiber and a preparation method thereof, and belongs to the technical field of fiber preparation. Background Art

[0002] Thermotropic liquid crystal polyarylate (LCP) is anisotropic in the solid state, but can form orderly arranged liquid crystals in the molten state and be made into fibers by melt spinning. Through melt blending modification, the strength and elasticity of the composite material can be improved, and LCP fibers with better performance can be prepared. LCP fiber belongs to the category of high-performance fibers. It is a high-strength, high-modulus, low-creep fiber at high temperatures with excellent heat resistance, chemical corrosion resistance and hydrolysis resistance. In addition, LCP fiber also has excellent flame retardant and dielectric properties and good friction resistance and cutting resistance. It has a growing and huge application demand in the fields of national defense, aerospace, 5G communications, automotive electronics, etc. The development of high-performance LCP fibers is of great practical significance to improving my country's competitiveness in the above-mentioned important fields.

[0003] Celanese Corporation of the United States successfully developed Vectran fiber in the 1980s. Kuraray Corporation of Japan introduced this technology and realized the industrial production of Vectran thermotropic liquid crystal fiber in early 1990, with a production capacity of 400 t / a, becoming the world's first industrial production line for liquid crystal polyester fiber. Currently, the production capacity of Vectran fiber has exceeded 2,000 t / a.

[0004] Commercially available LCP is often divided into three types according to the heat deformation temperature under a load of 1.86 MPa: high temperature resistant (Type I), medium temperature resistant (Type II), and low temperature resistant (Type III). About 60% of commercial LCP fibers are made of Type II LCP. This is because melt spinning requires that the thermal decomposition temperature of the fiber-forming polymer must be much higher than its melting point to ensure that the polymer does not decompose during the processing and maintain a wide processing window. During the melt spinning process, when the LCP melt is extruded through the spinneret, the liquid crystal macromolecules are oriented along the flow direction (fiber axis) under the action of shear force. After the fiber is cooled and solidified, this oriented structure is stabilized, showing high strength and high modulus properties. The main component of LCP is para-hydroxybenzoic acid (HBA), but HBA homopolymers are highly crystalline and cannot be processed using conventional technology. The melting point of the polymer can usually be reduced by increasing the transition entropy, reducing the transition enthalpy, or a combination of the two. Introducing flexible segments or side chains into the molecule not only reduces the linearity of the macromolecule but also acts as a plasticizer. Therefore, copolymerization of HBA with different second components can produce LCP with different heat resistance temperatures, such as Vectran, which is produced by random copolymerization of HBA and 2-hydroxy-6-naphthoic acid (HNA). The introduction of HNA units into the macromolecular chain destroys the orderly stacking of HBA units, thereby reducing the melting point. The following table shows the types of LCP fibers and representative products on the market:

[0005]

[0006] LCP fiber has excellent properties such as high strength, high modulus, low density, good stability, and corrosion resistance. It has been widely used in special ropes and cables (military, marine), aerospace (airships, aerostat skins, balloon membranes), information communications (signal lines, headphone lines), safety protection, sports and leisure, etc. Due to the high proportion of inert aromatic rings in the fiber, the fiber surface is smooth and has poor adhesion to other materials, which limits its use. Therefore, it is particularly important to modify the fiber surface to improve its bonding ability with the matrix. Summary of the invention

[0007] The present invention aims at the deficiencies in the prior art and provides a liquid crystal polyarylate polymer, a liquid crystal polyarylate fiber and a preparation method thereof. The repeating unit structure of the liquid crystal polyarylate contains polar groups, which greatly enhance the adhesion of the fiber through dipole interaction and hydrogen bond interaction.

[0008] The technical solution of the present invention to solve the above technical problems is as follows: a liquid crystal polyarylate polymer, wherein the macromolecular chain of the liquid crystal polyarylate polymer includes the following three structural units:

[0009] ;

[0010] The R 1 , R 2 , R3 , R 4 are independently selected from H or F, and the R 1 , R 2 , R 3 , R 4 At least one of them is F; the L is selected from any one of the following structures:

[0011] .

[0012] Furthermore, the structural unit III is derived from at least one of the following fluorinated benzoic acid monomers:

[0013] .

[0014] The present invention also discloses a method for preparing a liquid crystal polyarylate polymer, the preparation method comprising:

[0015] S1-1, under an inert gas atmosphere, adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer, 2-hydroxy-6-naphthoic acid, and a catalyst to acetic anhydride, and heating to perform a prepolymerization reaction;

[0016] S1-2. After the prepolymerization reaction is completed, the inert gas atmosphere is maintained, the temperature is raised to carry out the polycondensation reaction, acetic anhydride is continuously discharged during the polycondensation reaction to control the viscosity of the reaction polymer, and the liquid crystal polyarylate polymer is obtained after the reaction is completed.

[0017] Furthermore, in step S1-1, the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer, and 2-hydroxy-6-naphthoic acid is (2-5): (0.4-3): 1;

[0018] The added amount of the catalyst is 0.001%-0.005% of the molar amount of the 2-hydroxy-6-naphthoic acid.

[0019] Furthermore, in step S1-1, the catalyst is at least one of cupric acetate, ferric chloride, ferric acetate, zinc chloride, zinc acetate, aluminum chloride, magnesium chloride, cupric chloride, cobalt chloride, cobalt acetate, and manganese acetate.

[0020] Furthermore, in step S1-1, the prepolymerization reaction temperature is 120-160° C., and the prepolymerization reaction time is 1.5-2.5 h;

[0021] In step S1-2, the polycondensation reaction temperature is 260-320°C, and the polycondensation reaction time is 1.5-2.5h.

[0022] Furthermore, in step S1-2, the intrinsic viscosity of the liquid crystal polyarylate polymer at 30° C. is 3.0-6.0 dL / g.

[0023] The present invention also discloses a liquid crystal polyarylate fiber, which is obtained by melt spinning the liquid crystal polyarylate polymer of the present invention. The liquid crystal polyarylate fiber has a tensile strength of 27-30 cN / dtex, an elastic modulus of 135-145 GPa, and an elongation at break of 4-7%.

[0024] The present invention also discloses a method for preparing liquid crystal polyarylate fiber, the preparation method comprising:

[0025] S2-1, the liquid crystal polyarylate polymer is subjected to twin-screw extrusion, granulation, and then to a strand drying process to obtain a polymer slice for spinning;

[0026] S2-2, the polymer slices are melt-spun to obtain liquid crystal polyarylate primary fibers of different deniers;

[0027] S2-3, the liquid crystal polyarylate primary fibers are subjected to high temperature heat treatment to obtain the liquid crystal polyarylate fibers.

[0028] Further, in step S2-1, the temperature of the twin-screw extruder is 240-300°C;

[0029] In step S2-2, the melt spinning temperature is 290-350°C, and the melt spinning draft ratio is 15-35 times;

[0030] In step S2-3, the high temperature heat treatment temperature is 240-320°C.

[0031] The beneficial effects of the present invention are:

[0032] The present invention prepares a high-strength and high-modulus liquid crystal polyarylate fiber by melt polymerization and melt spinning. The high strength and high modulus of the fiber are derived from the electrostatic interaction and hydrogen bond interaction between macromolecular chains. Fluorine atoms are the most electronegative element in the periodic table. Due to the introduction of fluorine atoms, the electrostatic interaction between fluorine atoms and other atoms (such as oxygen atoms) and the hydrogen bond interaction between fluorine atoms and hydrogen atoms make the interaction between macromolecular chains stronger, which is beneficial to improving the tensile strength and modulus of the fiber.

[0033] The introduction of structural units containing fluorine atoms in the liquid crystal polyarylate polymer of the present invention, combined with appropriate polymerization conditions and melt spinning conditions, makes the surface adhesion of the liquid crystal polyarylate fiber stronger. Also by utilizing the extremely strong electronegativity of fluorine atoms, when a composite material is made with other resins or materials, the dipole interaction and hydrogen bond interaction between the fluorine atoms and the other resins make the performance of the composite material more excellent.

[0034] In summary, the liquid crystal polyarylate fiber of the present invention has good mechanical properties and low water absorption, and its excellent interface composite properties make it have high adhesion with other materials, and has broad application prospects in the fields of 5G communications. DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0037] A liquid crystal polyarylate polymer, wherein the macromolecular chain of the liquid crystal polyarylate polymer comprises the following three structural units:

[0038] ;

[0039] The R 1 , R 2 , R 3 , R 4 are independently selected from H or F, and the R 1 , R 2 , R 3 , R 4 At least one of them is F; the L is selected from any one of the following structures:

[0040] .

[0041] Among them, m, n, and p in the structural unit are natural numbers greater than 0, which only represent that these structural units are repetitive in the final liquid crystal polyarylate polymer.

[0042] Specifically, the structural unit III is derived from at least one of the following fluorinated benzoic acid monomers:

[0043] .

[0044] A method for preparing a liquid crystal polyarylate polymer, the preparation method comprising:

[0045] S1-1, under an inert gas atmosphere, adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer, 2-hydroxy-6-naphthoic acid, and a catalyst to acetic anhydride, and heating to perform a prepolymerization reaction;

[0046] S1-2. After the prepolymerization reaction is completed, the inert gas atmosphere is maintained, the temperature is raised to carry out the polycondensation reaction, acetic anhydride is continuously discharged during the polycondensation reaction to control the viscosity of the reaction polymer, and the material is discharged after the reaction is completed to obtain the liquid crystal polyarylate polymer.

[0047] Specifically, in step S1-1, the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer, and 2-hydroxy-6-naphthoic acid is (2-5): (0.4-3): 1;

[0048] The added amount of the catalyst is 0.001%-0.005% of the molar amount of the 2-hydroxy-6-naphthoic acid.

[0049] Specifically, in step S1-1, the catalyst is at least one of cupric acetate, ferric chloride, ferric acetate, zinc chloride, zinc acetate, aluminum chloride, magnesium chloride, cupric chloride, cobalt chloride, cobalt acetate, and manganese acetate.

[0050] Specifically, in step S1-1, the prepolymerization reaction temperature is 120-160° C., and the prepolymerization reaction time is 1.5-2.5 h;

[0051] In step S1-2, the polycondensation reaction temperature is 260-320°C, and the polycondensation reaction time is 1.5-2.5h.

[0052] Specifically, in step S1-2, the intrinsic viscosity of the liquid crystal polyarylate polymer at 30° C. is 3.0-6.0 dL / g.

[0053] A liquid crystal polyarylate fiber, which is obtained by melt spinning the liquid crystal polyarylate polymer of the present invention, and has a tensile strength of 27-30 cN / dtex, an elastic modulus of 135-145 GPa, and an elongation at break of 4-7%.

[0054] A method for preparing liquid crystal polyarylate fiber, the preparation method comprising:

[0055] S2-1, the liquid crystal polyarylate polymer is subjected to twin-screw extrusion, granulation, and then to a strand drying process to obtain a polymer slice for spinning;

[0056] S2-2, the polymer slices are melt-spun to obtain liquid crystal polyarylate primary fibers of different deniers;

[0057] S2-3, the liquid crystal polyarylate primary fibers are subjected to high temperature heat treatment to obtain the liquid crystal polyarylate fibers.

[0058] Specifically, in step S2-1, the temperature of the twin-screw extruder is 240-300°C;

[0059] In step S2-2, the melt spinning temperature is 290-350°C, and the melt spinning draft ratio is 15-35 times;

[0060] In step S2-3, the high temperature heat treatment temperature is 240-320°C.

[0061] The test methods involved in the following embodiments are:

[0062] (1) Intrinsic viscosity test method: weigh 0.1250 g of sample into a conical flask, add 25 ml of pentafluorophenol solvent, and stir magnetically at room temperature until completely dissolved; control the water bath temperature at 30±0.2℃; rinse the Ubbelohde viscometer with pentafluorophenol, keep the temperature constant for ten minutes, and measure the blank outflow time t 0 ; Rinse the Ubbelohde viscometer with the sample to be tested, keep the temperature constant for ten minutes, and measure the outflow time t 1 ; According to the formula IV=0.5ln(t 1 / t 0 ) Calculate the intrinsic viscosity IV of the sample to be tested.

[0063] (2) Test standard for liquid crystal polyarylate fiber index: GB / T 42823-2023, test method: First weigh a certain amount of fiber filaments, test the linear density of the fiber, and then set the twist according to the linear density for twisting. Fix the twisted fiber on the tensile test fixture, measure the mechanical properties 10 times, and take the average value. The electric tensile machine model is Instron 34TM-30.

[0064] (3) Adhesion test of liquid crystal polyarylate fiber: According to the standard JC / T 773-2010, the pull-out test of liquid crystal polyarylate fiber in resin was carried out. The resin was prepared according to the weight ratio of epoxy resin GCC-135: curing agent GCC-137 = 100:30, and injected into the fiber extraction device to test the extraction force.

[0065] Example 1

[0066] The fluorinated benzoic acid monomer used is: .

[0067] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 2.7:0.6:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0068] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 260° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 3.0 dL / g was obtained.

[0069] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 250°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0070] The nascent fibers are heat treated at 240°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0071] Example 2

[0072] The fluorinated benzoic acid monomer used is: .

[0073] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 2.7:0.54:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0074] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 280° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 4.5 dL / g was obtained.

[0075] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 250°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0076] The nascent fibers are heat treated at 240°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0077] Example 3

[0078] The fluorinated benzoic acid monomer used is: .

[0079] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 2.7:0.49:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0080] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 260° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 6.0 dL / g was obtained.

[0081] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 300°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0082] The nascent fibers are heat treated at 320°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0083] Example 4

[0084] The fluorinated benzoic acid monomer used is: .

[0085] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 2.7:0.4:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0086] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 260° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 5.0 dL / g was obtained.

[0087] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 250°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0088] The nascent fibers are heat treated at 240°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0089] Example 5

[0090] The fluorinated benzoic acid monomer used is: .

[0091] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid into an acetic anhydride solution containing zinc chloride in a mass fraction, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 5:2:1, and the amount of zinc chloride added is 0.002% of the mass of 2-hydroxy-6-naphthoic acid;

[0092] Under nitrogen protection, the temperature was slowly raised to 120° C., and the prepolymerization reaction was carried out for 2.5 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 320° C. under nitrogen protection, and the polycondensation reaction was carried out for 1.5 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 4.5 dL / g was obtained.

[0093] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 280°C and melt-spun at 350°C with a drafting ratio of 35 times to obtain liquid crystal polyarylate primary fibers.

[0094] The nascent fibers are heat treated at 300°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0095] Example 6

[0096] The fluorinated benzoic acid monomer used is: .

[0097] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing zinc acetate by mass, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 2:1:1, and the amount of zinc acetate added is 0.005% of the mass of 2-hydroxy-6-naphthoic acid;

[0098] Under nitrogen protection, the temperature was slowly raised to 140°C, and the prepolymerization reaction was carried out for 1.5 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 300°C under nitrogen protection, and the polycondensation reaction was carried out for 2.5 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 5.5 dL / g was obtained.

[0099] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 260°C and melt-spun at 320°C with a drafting ratio of 20 times to obtain liquid crystal polyarylate primary fibers.

[0100] The nascent fibers are heat treated at 280°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0101] Example 7

[0102] The fluorinated benzoic acid monomer used is: .

[0103] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid into an acetic anhydride solution containing magnesium chloride in a mass fraction, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 3:0.8:1, and the amount of magnesium chloride added is 0.002% of the mass of 2-hydroxy-6-naphthoic acid;

[0104] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 280° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 5.0 dL / g was obtained.

[0105] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 280°C and melt-spun at 300°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0106] The nascent fibers are heat treated at 260°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0107] Comparative Example 1

[0108] Liquid crystal polyarylate fibers were prepared by the same method as in Example 4, except that p-hydroxybenzoic acid in the same molar amount as the fluorinated benzoic acid monomer was added instead of the fluorinated benzoic acid monomer. The specific preparation process is as follows:

[0109] (1) adding p-hydroxybenzoic acid and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid to 2-hydroxy-6-naphthoic acid is 3.1:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0110] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 260° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 3.5 dL / g was obtained.

[0111] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 250°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0112] The nascent fibers are heat treated at 240°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0113] Comparative Example 2

[0114] The liquid crystal polyarylate fiber was prepared by the same method as in Example 4, except that the amount of the fluorinated benzoic acid monomer was increased. The specific preparation process is as follows:

[0115] The fluorinated benzoic acid monomer used is: .

[0116] (1) adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid, fluorinated benzoic acid monomer and 2-hydroxy-6-naphthoic acid is 2.7:3:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0117] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 260° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 5.6 dL / g was obtained.

[0118] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 250°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0119] The nascent fibers are heat treated at 240°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0120] Comparative Example 3

[0121] Liquid crystal polyarylate fibers were prepared by the same method as in Example 3, except that the fluorinated benzoic acid monomer was replaced by: (4-hydroxy-2-trifluoromethylbenzoic acid), the specific preparation process is:

[0122] (1) adding p-hydroxybenzoic acid, 4-hydroxy-2-trifluoromethylbenzoic acid and 2-hydroxy-6-naphthoic acid to an acetic anhydride solution containing copper acetate, wherein the molar ratio of p-hydroxybenzoic acid, 4-hydroxy-2-trifluoromethylbenzoic acid and 2-hydroxy-6-naphthoic acid is 2.7:0.49:1, and the amount of copper acetate added is 0.001% of the mass of 2-hydroxy-6-naphthoic acid;

[0123] Under nitrogen protection, the temperature was slowly raised to 160° C., and the prepolymerization reaction was carried out for 2 hours. After the reaction was completed, the prepolymerization product was transferred to a polycondensation reactor, and the temperature in the reactor was raised to 260° C. under nitrogen protection, and the polycondensation reaction was carried out for 2 hours. After the reaction was completed, a liquid crystal polyarylate polymer with a polymer viscosity of 5.8 dL / g was obtained.

[0124] (2) The liquid crystal polyarylate polymer was subjected to a twin-screw degassing treatment at 300°C and melt-spun at 290°C with a drafting ratio of 15 times to obtain liquid crystal polyarylate primary fibers.

[0125] The nascent fibers are heat treated at 320°C, then oiled, and collected into rolls to obtain LCP finished fibers (liquid crystal polyarylate fibers).

[0126] Comparative Example 4

[0127] Liquid crystal polyarylate polymer was prepared by the same method as in Example 1, except that: in step (1), the polycondensation reaction temperature was lowered. In this comparative example 4, the polycondensation reaction temperature was 240°C. It was found in the experiment that the polymerization reaction was incomplete, and the viscosity of the obtained polymer was 2.9 dL / g. LCP fibers were obtained by spinning.

[0128] Comparative Example 5

[0129] Liquid crystal polyarylate fibers were prepared by the same method as in Example 1, except that in step (2), the melt spinning temperature was lowered. In Comparative Example 5, the melt spinning temperature was 270°C. It was found in the experiment that the spinnability of the fibers was poor and more fiber breakage problems occurred during the spinning process.

[0130] Comparative Example 6

[0131] Liquid crystal polyarylate fibers were prepared by the same method as in Example 1, except that in step (2), the heat treatment temperature was lowered. In Comparative Example 6, the heat treatment temperature was 220°C.

[0132] The performance of the liquid crystal polyarylate fibers prepared in the above examples and comparative examples was tested. The specific test results are shown in Table 1 below.

[0133] Table 1 Performance test data of liquid crystal polyarylate fiber

[0134]

[0135] It can be seen from the data in the above table that the liquid crystal polyarylate fibers prepared by the preparation method of Examples 1-7 using the present invention have good mechanical properties and high adhesion to composite materials, and have broad application prospects in the fields of 5G communications.

[0136] From the comparison of the experimental data of Example 4 and Comparative Example 1, it can be seen that the introduction of the fluorinated benzoic acid monomer of the present invention in the preparation process of liquid crystal polyarylate fiber will make the LCP fiber have very good composite bonding performance. Compared with conventional liquid crystal polyarylate fiber, the pull-out force of the liquid crystal polyarylate fiber of the present invention is increased by nearly three times; because of the presence of the strongly electronegative heteroatom fluorine atom in the fiber, the bonding force between the fiber and the epoxy resin is enhanced through the intermolecular hydrogen bond interaction and polar interaction. In addition, the mechanical properties of the fiber, such as tensile strength and elastic modulus, are also greatly improved compared with the unmodified LCP fiber.

[0137] From the comparison of the experimental data of Example 4 and Comparative Example 2, it can be seen that if the addition ratio of the fluorinated benzoic acid monomer is too high, the performance of the liquid crystal polyarylate fiber will be reduced. If the addition amount of the fluorinated benzoic acid monomer is too much, the regularity of the molecular chain will be destroyed, resulting in a decrease in the crystallinity of the fiber, thereby causing a decrease in the mechanical properties. Therefore, the use of the fluorinated benzoic acid monomer dosage ratio defined in the present invention is more conducive to obtaining liquid crystal polyarylate fibers with excellent performance.

[0138] From the comparison of the experimental data of Example 3 and Comparative Example 3, it can be seen that if the type of fluorine-containing benzoic acid monomer is replaced, the performance of the liquid crystal polyarylate fiber will also be reduced. Compared with a single fluorine atom, due to the larger volume of the trifluoromethyl group, the introduction of the trifluoromethyl group will lead to a weakening of the interaction between the molecular chains, resulting in a decrease in the mechanical properties of the fiber. The use of the fluorine-containing benzoic acid monomer defined in the present invention is more conducive to obtaining liquid crystal polyarylate fibers with excellent performance.

[0139] From the comparison of the experimental conditions of Example 1 and Comparative Example 4, it can be seen that if the polycondensation temperature decreases, the molecular weight of the polymer of the liquid crystal polyarylate slice will be low, thereby reducing the mechanical properties of the fiber.

[0140] From the comparison of the experimental conditions of Example 1 and Comparative Example 5, it can be seen that the increase in melt spinning temperature will cause the polymer resin to degrade when passing through the spinning equipment, thereby increasing the number of broken fibers and the phenomenon of seizure in the spun fibers, and it is impossible to prepare qualified finished liquid crystal polyarylate fibers. Only by introducing fluorobenzoic acid structural units into the polymer and matching the appropriate polycondensation temperature and melt spinning temperature can liquid crystal polyarylate fibers with excellent performance be obtained.

[0141] From the comparison of the experimental conditions of Example 1 and Comparative Example 6, it can be seen that if the heat treatment temperature is lowered, the performance of the liquid crystal polyarylate fiber will also be reduced. The heat treatment process of the liquid crystal polyarylate fiber involves a solid phase viscosity enhancement process. During the solid phase viscosity enhancement process, the macromolecular chains in the polymer continue to undergo chemical reactions. When the heat treatment temperature is reduced, the energy provided is insufficient to induce the chemical reaction in the solid phase viscosity enhancement process, so that the mechanical properties of the finished liquid crystal polyarylate fiber do not meet the requirements.

[0142] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0143] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A liquid crystal polyarylate fiber, characterized in that: The liquid crystal polyarylate fiber is prepared by melt spinning a liquid crystal polyarylate polymer, and the liquid crystal polyarylate fiber has a tensile strength of 27-30 cN / dtex, an elastic modulus of 135-145 GPa, and an elongation at break of 4-7%; The preparation method of the liquid crystal polyarylate fiber is: S2-1, the liquid crystal polyarylate polymer is subjected to twin-screw extrusion, granulation, and then to a strand drying process to obtain a polymer slice for spinning; S2-2, the polymer slices are melt-spun to obtain liquid crystal polyarylate primary fibers of different deniers; S2-3, subjecting the liquid crystal polyarylate nascent fibers to high temperature heat treatment to obtain the liquid crystal polyarylate fibers; In step S2-1, the temperature of the twin-screw extruder is 240-300°C; In step S2-2, the melt spinning temperature is 290-350°C, and the melt spinning draft ratio is 15-35 times; In step S2-3, the high temperature heat treatment temperature is 240-320°C; The macromolecular chain of the liquid crystal polyarylate polymer consists of the following three structural units composition: ; The R1, R2, R3, and R4 are each independently selected from H or F, and at least one of the R1, R2, R3, and R4 is F; and the L is: ; The preparation method of the liquid crystal polyarylate polymer is: S1-1, under an inert gas atmosphere, adding p-hydroxybenzoic acid, fluorinated benzoic acid monomer, 2-hydroxy-6-naphthoic acid, and a catalyst to acetic anhydride, and heating to perform a prepolymerization reaction; S1-2, after the prepolymerization reaction is completed, maintaining an inert gas atmosphere, raising the temperature to carry out a polycondensation reaction, continuously discharging acetic anhydride during the polycondensation reaction to control the viscosity of the reaction polymer, and obtaining the liquid crystal polyarylate polymer after the reaction is completed; The molar ratio of the p-hydroxybenzoic acid, the fluorinated benzoic acid monomer and the 2-hydroxy-6-naphthoic acid is (2-5):0.4:

1.

2. The liquid crystal polyarylate fiber according to claim 1, characterized in that: The structural unit III is derived from at least one of the following fluorinated benzoic acid monomers: 。 3. The liquid crystal polyarylate fiber according to claim 1, characterized in that: In step S1-1, the amount of the catalyst added is 0.001%-0.005% of the molar amount of the 2-hydroxy-6-naphthoic acid.

4. The liquid crystal polyarylate fiber according to claim 1, characterized in that: In step S1-1, the catalyst is at least one of cupric acetate, ferric chloride, ferric acetate, zinc chloride, zinc acetate, aluminum chloride, magnesium chloride, cupric chloride, cobalt chloride, cobalt acetate, and manganese acetate.

5. The liquid crystal polyarylate fiber according to claim 1, characterized in that: In step S1-1, the prepolymerization temperature is 120-160° C., and the prepolymerization time is 1.5-2.5 h; In step S1-2, the polycondensation reaction temperature is 260-320°C, and the polycondensation reaction time is 1.5-2.5h.

6. The liquid crystal polyarylate fiber according to claim 1, characterized in that: In step S1-2, the intrinsic viscosity of the liquid crystal polyarylate polymer at 30° C. is 3.0-6.0 dL / g.

Citation Information

Patent Citations

  • High-toughness liquid crystal polymer film and preparation method thereof

    CN113604009A

  • High-performance liquid crystal polyarylate fiber as well as preparation method and production equipment thereof

    CN114134590A